How to scale up effective international climate finance by the EU? Tax coalitions and jurisdictional reward funds for the case of fossil fuel - Ottmar Edenhofer; Matthias Kalkuhl; Lennart Stern (Kiel Institute for the World Economy (IfW Kiel), 2025)
This paper examines how donor countries can be motivated by self-interest to fund emission reductions in low- and middle-income countries (LMICs). While not solving the broader climate cooperation problem, we propose pragmatic measures that do not require global consensus on future climate risks or binding commitments. We quantify the unilateral benefits for donors - reduced climate damages and improved terms-of-trade from lower fossil fuel prices - resulting from financing fossil fuel demand reductions. To address project-level finance inefficiencies, we introduce jurisdictional reward funds targeting governments, which also generate implicit wealth transfers to LMICs. A self-enforcing coalition of fossil fuel importers, such as the European Union and China, could mobilize USD 66 billion annually for mitigation in LMICs, cutting emissions by 1060 Mt CO₂ per year and transferring USD 33 billion per year. LMICs additionally benefit from USD 78 billion in reduced climate damages and USD 19 billion from lower fuel prices. We explore coalition stability, geopolitical considerations, and how broader tax and reward mechanisms could further improve global climate, forest, and health outcomes.
Keywords: H23; H87; F55; Q41; 330; Jurisdictional Reward Funds; tax coalitions; fuel market leakage; global public goods; terms-of-trade effects; demand-side climate policy